THE ROLE OF DUOLINGO APPLICATION TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT JUNIOR HIGH SCHOOL IN ACADEMIC YEAR 2023/2024 - Shinta Shofia Ananda; Arso Setiaji; Indri Kustantinah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT Learning is essential; we must comprehend technology in today's fast-paced technological society. Regarding education, it is very simple for us to learn a new language using our cell phones. Duolingo is a language-learning program that allows students to learn English through translation, comparing, dictation, fill-in-the-blank, speaking, listening, multiple choice, and competition. Therefore, this research analyses the implementation of Duolingo in language learning and its potential for facilitating the full development of the English language. The study discovered that using the Duolingo application was highly successful at strengthening students' interest in learning English: two classes, each containing 30 students who participated. Two groups, the experimental class and the control class, are involved in this investigation. Based on this study, Duolingo is an app where any newcomer can begin learning an additional language because it encourages them to keep learning. Keywords: Duolingo application; Vocabulary, Educational Language Tool